Women in War: Being Protected or Combatant? - Indrawan, Jerry (Jurnal Hubungan Internasional, 2015)
In war or other armed conflicts, generally women are categorized as vulnerable people. Sexual violence and harassment towards women is frequently use as a technique to committed torture against them. The torture are meant to create terror or as one of the methods of ethnic cleansing. Considering that women could be categorized as combatant in certain situation and seeing the development in internal armed conflict that allowed women to participate in hostile situation as combatant, this paper would like to give an overview towards women position in war and armed conflicts related to international humanitarian law.